Biocompatibility of supercritical carbon dioxide processed poly(lactide-co-glycolide) and poly(ε-caprolactone) assessed with primary human osteoblasts: Biokompatibilnost z metodo superkritičnega ogljikovega dioksida procesiranih poli(laktid-ko-glikolida) in poli(ε-kaprolaktona) na primarnih človeških osteoblastih - Dariš, Barbara; Ferk, Polonca; Markočič, Elena; Knez, Željko (Acta Medico-Biotechnica, 2021)
Purpose: In the present study, poly (lactide-co-glycolide) (PLGA) and poly (ε-caprolactone) (PCL) combined with hydroxyapatite (HA) were processed with supercritical CO2 (scCO2) to obtain macroporous foams.Methods: The in vitro biocompatibility and mineralization of the foams was assessed with primary human osteoblasts (HOB).Results: The WST-8 (Water-soluble Tetrazolium salts) test for cell proliferation activity and alkaline phosphatase (ALP) activity assay were used to estimate HOB proliferation and differentiation respectively. The proliferation activity of HOB on foamed PLGA and PCL decreased compared to non-foamed polymer, while on PLGA and PCL foamed constructs with hydroxyapatite (HA), the proliferation activity increased compared to the foamed PLGA and PCL.Conclusions: The ALP activity on PLGA, PCL and foamed PCL was similar to the control, being less intense on PCL foamed constructs with HA, while foamed PLGA and PLGA foamed constructs with HA showed no evidence of ALP activity.
Keywords: Biocompatibility; supercritical carbon dioxide foaming; poly(lactide-co-glycolide); poly(εcaprolactone); primary human osteoblasts